Applicability of analytical protocols for the characterisation of carbon-supported platinum group metal fuel cell electrocatalysts - M. Williams; L. Khotseng; Q. Naidoo; L. Petrik; A. Nechaev; V. Linkov (South African Journal of Science)
The nanoparticulate size of fuel cell electrocatalysts raises significant challenges in the analytical techniques used in their structural and electrochemical characterisation. For this reason, the applicability of analytical protocols in the qualitative and quantitative characterisation of nanophase fuel cell electrocatalysts was investigated. A set of structural and chemical properties influencing the performance of the electrocatalysts was identified. A large range of analytical tools was employed in characterising the electrocatalysts of interest. High accuracy and precision in the quantitative and qualitative structural and electrochemical characterisation of Pt/C and Pt-Ru/C nanophase electrocatalysts was demonstrated. Certain techniques were deemed to be highly applicable in discriminating between high- and low-performance electrocatalysts based on their structural and electrochemical properties. The goal of this effort is to contribute to the development of South Africa's capabilities in the emerging hydrogen economy.